Managing and preventing prostate disorders the natural alternatives - Redmon, George L. (HOHM Press, 2000)
Assessing who is at risk from prostate disorder, and offering information on prevention, the author shows how mind, body and emotions interact with and promote the overall health of the immune system. He offers a 25-step wellness plan.